Village ecosystem vulnerability in karst desertification control: evidence from South China Karst - Tang, Jiuhan; Xiong, Kangning; Wang, Qi; Chen, Yue; Wu, Qinglin (Frontiers in Ecology and Evolution, 2023)
Under the background of global environment changes and the intensification of human activities, village ecosystems are facing enormous impacts. In particular, the rural areas in the South China Karst are facing the serious problems such as karst desertification and human-land conflicts. In recent decades, the Chinese government and scientific researchers have been committed to control the karst desertification. However, the village ecosystem in the context of karst desertification control is still fragile. In order to promote the sustainable development of villages in the karst desertification control. This paper takes village ecosystems of different karst desertification area as study case to clarify their vulnerability level and vulnerability driving factors for put forward adaptive governance strategies. We found that (1) The vulnerability level of villages ecosystem of the karst desertification control is different. Villages ecosystem are mildly vulnerable in the none-potential karst desertification control area, villages ecosystem are moderately vulnerable in potential-mild area, and the villages ecosystem are moderately and high vulnerable in moderate-severe karst desertification control areas. (2) The combined effects of natural environment and human activities have led to the vulnerability of villages ecosystem in karst desertification control in the South China Karst. Among them, topography, climate, forest coverage, landscape pattern, soil erosion, karst desertification, economic development level and production and living activities are the main factors affecting villages ecosystem vulnerability of karst desertification control in the South China Karst, the differences of these factors lead to village ecosystem vulnerability levels is different. (3) We designed adaptive governance strategies for village ecosystems based on the characteristics and vulnerability influencing factors of village ecosystems in different karst desertification, with sustainable development as the goal. It provide decision-making basis for promoting the sustainable development of the village ecosystem in the karst desertification control.